The difference in def-t and DMF-T index between autistic and normal children - Gayatri, Prima Abigail; Herdiyati, Yetty; Chemiawan, Eka (Universitas Padjadjaran, 2013)
Introduction: One of the problems in the development of a child is autism. Children with autism have limitations in social interaction and communication. There are differences in parenting and food consumption between normal and autistic children that may lead to differences in caries activity. The research was conducted in order to obtain the difference of index def-t and DMF-T between children with autism and normal children. Methods: This study was performed as a cross-sectional analytical research, using equality of two proportions and Mann-Whitney to analyze the differences of index def-t and DMF-T index children with autism and normal children. The research sample consisted of 23 children with autism of Yayasan Our Dream, Yayasan Pelita Hafizh and SLB Prananda and 23 normal children of MI Cikapayang. Results: The results of this research showed that the index def-t of children with autism was 1.21 and normal children was 3.69. The DMF-T index of children with autism was 1.56, while the normal children was 2.26. Conclusion: The conclusion of this research was that there was no significant difference in def-t index in children with autism and normal children except for the